Role of Interferon‐γ–Producing Th1 Cells in a Murine Model of Type I Interferon–Independent Autoinflammation Resulting From DNase II Deficiency. Issue 2 (29th December 2019) - Pawaria, Sudesh; Nündel, Kerstin; Gao, Kevin M.; Moses, Stephanie; Busto, Patricia; Holt, Kevin; Sharma, Rohit B.; Brehm, Michael A.; Gravallese, Ellen M.; Socolovsky, Merav; Christ, Anette; Marshak‐Rothstein, Ann
Abstract : Objective: Patients with hypomorphic mutations in DNase II develop a severe and debilitating autoinflammatory disease. This study was undertaken to compare the disease parameters in these patients to those in a murine model of DNase II deficiency, and to evaluate the role of specific nucleic acid sensors and identify the cell types responsible for driving the autoinflammatory response. Methods: To avoid embryonic death, Dnase2 −/− mice were intercrossed with mice that lacked the type I interferon (IFN) receptor ( Ifnar −/− ). The hematologic changes and immune status of these mice were evaluated using complete blood cell counts, flow cytometry, serum cytokine enzyme‐linked immunosorbent assays, and liver histology. Effector cell activity was determined by transferring T cells from Dnase2 −/− × Ifnar −/− double‐knockout (DKO) mice into Rag1 −/− mice, and 4 weeks after cell transfer, induced changes were assessed in the recipient mice. Results: In Dnase2 −/− × Ifnar −/− DKO mice, many of the disease features found in DNase II–deficient patients were recapitulated, including cytopenia, extramedullary hematopoiesis, and liver fibrosis. Dnase2 +/+ × Rag1 −/− mice (n > 22) developed a hematologic disorder that was attributed to the transfer of an unusual IFNγ‐producing T cell subset from the spleens of donor Dnase2 −/− × Ifnar −/− DKO mice. Autoinflammation in this murine model did not depend on the stimulator of IFN genes (STING) pathway but was highly dependent on the chaperone protein Unc93B1. Conclusion: Dnase2 −/− × Ifnar −/− DKO mice may be a valid model for exploring the innate and adaptive immune mechanisms responsible for the autoinflammation similar to that seen in DNASE2 ‐hypomorphic patients. In this murine model, IFNγ is required for T cell activation and the development of clinical manifestations. The role of IFNγ in DNASE2 ‐deficient patient populations remains to be determined, but the ability of Dnase2 −/− mouse T cells to transfer disease to Rag1 −/− mice suggests that T cells may be a relevant therapeutic target in patients with IFN‐related systemic autoinflammatory diseases.